Developing the expertise of primary and elementary classroom teachers : professional learning for a changing world - Eaude, Tony (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2018)
"Developing the Expertise of Primary and Elementary Classroom Teachers challenges many current assumptions about primary education. Tony Eaude draws on the experiences of teachers at a range of career phases to show how primary classroom teachers need a wide repertoire of strategies and a flexible, reciprocal and intuitive approach to planning, assessment and teaching. He explores the way in which a deep understanding of how young children learn is needed, and an ability to create an inclusive environment, caring relationships and teachers attuned to children are essential. He shows that many of these elements are learned over time, through regular, sustained, contextualised opportunities, relating theory and practice, with the years soon after qualification particularly significant. Eaude argues that the constraints on manifesting expertise, many of which are emotional, must be overcome to develop qualities such as confidence and resilience, encourage informed intuition and create a secure professional identity. He highlights that the professional knowledge and judgement required in complex, changing situations is acquired and refined mainly through guided practice and experience backed by reflection and engagement with research. He emphasises the need for supportive professional learning communities and for policy to enable rather than constrain primary classroom teachers' enthusiasm, creativity and willingness to innovate, and an enriched apprenticeship model - using a mixture of processes, including observation of other teachers, practice, mentoring, case studies and discussion in professional communities"--